Working memory capacity, content familiarity, and university EFL students’ reading comprehension - Heriyawati, Dwi Fita; Saukah, Ali; Widiati, Utami (Universitas Pendidikan Indonesia, 2018)
This study explores the effect of working memory capacity (WMC) and content familiarity (CF) on EFL reading comprehension. Seventy senior students from a private university in Malang, Indonesia, were involved in the study, having been selected based on their English proficiency of at least pre-advanced level. These students were required to complete a reading span test for the WMC and a multiple-choice reading test based on CF. The findings of this study show that there is no interaction effect between WMC as the main independent variable and CF as the moderator variable; this implies that the students with higher WMC comprehend texts better than those with lower WMC, regardless of whether they are familiar or not with the texts.